Share

# If X = (6ab)/(A + B) Find the Value of (X + 3a)/(X - 3a) = (X + 3b)/(X - 3b) - Mathematics

Course
ConceptComponendo and Dividendo Properties

#### Question

if x = (6ab)/(a + b) find the value of (x + 3a)/(x - 3a) = (x + 3b)/(x - 3b)

#### Solution

x = (6ab)/(a + b)

=> x/(3a) = (2b)/(a + b)

Aplying compinendo and dividendo

(x + 3a)/(x - 3a) = (2b + a + b)/(2b - a - b)

(x + 3a)/(a - 3a) = (3b + a)/(b - a)  ...(1)

Again x = (6ab)/(a + b)

=> x/(3b) = (2a)/(a + b)

Applying componendo and dividendo

(x + 3b)/(x - 3b) = (2a + a + b)/(2a - a - b)

(x + 3b)/(x - 3b) = (3a + b)/(a - b)  ....(2)

From (1) and (2)

(x  + 3a)/(x - 3a) + (x + 3b)/(x - 3b) = (3b + a)/(b -a) + (3a + b)/(a - b)

(x + 3a)/(x - 3a) + (x + 3b)/(x - 3b) = (-3b -a + 3a + b)/(a - b)

(x + 3a)/(x - 3a) + (x + 3b)/(x - 3b) = (2a - 2b)/(a - b) = 2

Is there an error in this question or solution?

#### APPEARS IN

Selina Solution for Selina ICSE Concise Mathematics for Class 10 (2020 to Current)
Chapter 7: Ratio and Proportion (Including Properties and Uses)
Exercise 7(C) | Q: 6.1 | Page no. 101

#### Video TutorialsVIEW ALL [1]

Solution If X = (6ab)/(A + B) Find the Value of (X + 3a)/(X - 3a) = (X + 3b)/(X - 3b) Concept: Componendo and Dividendo Properties.
S